Augmented Reality (AR) And Virtual Reality (VR) Applications In Tourism: Embracing Emerging Technologies For Improved Tourist Experiences In Malaysian Tourism Industry - Juhanita Jiman; Salamiah Muhd Kulal (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This paper investigates the impact of Augmented Reality (AR) and Virtual Reality (VR) on the Malaysian tourism business. AR and VR have emerged as revolutionary forces, transforming a wide range of industries, with tourism at the forefront of this digital transition. Augmented Reality complements real-world experiences by superimposing digital information on top of the physical world, whereas Virtual Reality immerses users in simulated environment. AR and VR have completely transformed the tourist experience, including planning, booking, on-site exploration, and post-trip comments. AR applications enrich the tourist experience by providing interactive maps, historical insights, and real-time translations, whereas virtual reality (VR) technologies enable deep interaction in a variety of fascinating activities and provide a fascinating insight into the destination's attractions.